Quiet Eye: The next generation - comment on Vickers - Jörg Schroer; Judith Tirp; Rebecca Rienhoff (Bern Open Publishing, 2021)
In this commentary on Joan Vicker's target article (2016), we first recognize the work she has done in the last 35 years. We then provide examples of differentiations of the Quiet Eye (QE) that might be necessary to fully understand the multifacetedness of the phenomenon. Here we propose, as in our current review (Rienhoff, Tirp, Strauss, Baker, & Schorer, 2016), for the QE a differentiation by the mechanisms behind it. We suggest another categorization in the research on training the QE. Additionally, we provide further areas of research that are interesting for the future, namely the QE across life-span and the (in)dependence of the perceptual-motor processes.